DESIGN ASPECTS OF AGGREGATED COLD MIX ASBUTON SHEET ( ACAS ) - Dairi, Gompul
The thesis describes an investigation of factors influencing the design of Aggregated Cold Mix Asbuton Sheet (ACAS). Following preliminary investigation of the characteristics of the material to be used, the programme was carried out in three stages. Step 1 was concerned with establishing the optimum size of Asbuton particle to be used, also the compaction level and procedures to be followed. A constant bitumen content of 7% was chosen and the influence of curing-period duration was also studied. The results of stage 1 provided the bases for a detailed study in the stage 2 of the influence of bitumen content and curing period on mix characteristics, including resistance to water, as indicated by retained Marshall stability and indirect tensile strength. Stage 3 examined the Asbuton bitumen releaserate of a number of solvents, i.e. gasoline, kerosene, diesel fuel oil and BFO, and developed theoretical prediction of effective binder film-thickness when BFO is used as the solvent. The main conclusion of this thesis is that Bunker Fuel Oil (BFO) cannot function in the dual role of releasing bitumen and permanently softening it. It may be mixed with-Asbuton bitumen to produce a blend that satisfies normal binder requirement but in order to produce such a binder it must first release the bitumen from the Asbuton. This investigation indicates that the release rate of bitumen is extremely slow when BFO is used as the releasing agent and it is doubful if a "normal binder" ever results The poor performance of BFO in releasing bitumen has the further consequence that the densest aggregate gradation is not achieved. In essence, it is extremely difficult, if not impossible, to make a reasonable estimate at any time of the exact composition of the mix in terms of mineral constituent and effective binder.